Gender Differences in Quality-of-Life Outcome in Patients Undergoing Endoscopic Endonasal Skull Base Surgery - Tumlin, Parker; Al-Asadi, Zayd; Turner, Meghan; Ramadan, Hassan H.; Makary, Chadi A. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Background Prior studies showed that female patients with chronic rhinosinusitis (CRS) suffer a worse disease-specific quality of life (QoL).Goal The aim of this study is to investigate gender differences in sinonasal QoL outcomes in patients requiring endoscopic endonasal skull base surgeries (EESBS).Methods Cross-sectional analysis of patients presenting to our clinic from August 2020 to December 2022 with skull base tumors, spontaneous cerebrospinal fluid (CSF) rhinorrhea, or Grave's orbitopathy (for orbital decompression) was performed. Baseline and postsurgical QoL were measured using the 22-item Sinonasal Outcome Test (SNOT-22). Patients' demographics and comorbidities were reviewed. Patients with concomitant CRS were excluded.Results Eighty-six patients were included (54 with skull base tumors, 17 Grave's orbitopathy, and 15 spontaneous CSF rhinorrhea). The mean age of the patients was 52 years (range: 12.4–81.5 years), and 51.6% of the patients were females. There was no age difference between female and male patients. Smoking history, asthma, and allergic rhinitis were also similar between the two groups. Female patients had a significantly higher incidence of depression (58.3 vs. 32.4%, p = 0.018) and migraine (50.0 vs. 21.6%, p = 0.007). Female patients had a significantly worse overall SNOT-22 scores at baseline (33.6 vs. 18.2, p = 0.001), at the 3-month follow-up (29.7 vs. 15.5, p = 0.002), and at the 6-month follow-up (33.5 vs. 14.9, p = 0.005). This worse QoL was seen mainly in the ear/facial, sleep, and psychological domains. Linear regression of the SNOT-22 scores and its subdomains adjusting for comorbidities showed that migraine was found to be the most significant determinant of gender differences in the QoL.Conclusion Female patients who undergo EESBS show higher overall SNOT-22 scores secondary to higher incidence of migraine.
Keywords: patient-reported outcome measures; 22-item Sinonasal Outcome Test; skull base surgery; paranasal sinuses; gender